2007
DOI: 10.1177/0165025407074633
|View full text |Cite
|
Sign up to set email alerts
|

Socialization environments of Chinese and Euro-American middle-class babies: Parenting behaviors, verbal discourses and ethnotheories

Abstract: Children's socialization environments reflect cultural models of parenting. In particular, Euro-American and Chinese families have been described as following different socialization scripts. The present study assesses parenting behaviors as well as parenting ethnotheories with respect to three-month-old babies in middle-class families in Los Angeles and Beijing. Euro-American parents' behaviors towards their children, as well as their parental ethnotheories are assumed to express the cultural model of autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
4
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 44 publications
4
42
4
5
Order By: Relevance
“…Cross-cultural studies of mother-child conversations about past events have also shown that Asian mothers use less elaborate strategies to elicit speech from their children (Minami & McCabe, 1995;Mullen & Yi, 1995). Different socialization goals are linked to different performance in narratives produced by children from different cultures (Keller et al, 2007;Miller et al, 1997;Wang & Leichtman, 2000). For instance, Han et al (1998) demonstrated that the narratives of Chinese and Korean children were similarly less detailed in terms of specific events than those of American children.…”
mentioning
confidence: 99%
“…Cross-cultural studies of mother-child conversations about past events have also shown that Asian mothers use less elaborate strategies to elicit speech from their children (Minami & McCabe, 1995;Mullen & Yi, 1995). Different socialization goals are linked to different performance in narratives produced by children from different cultures (Keller et al, 2007;Miller et al, 1997;Wang & Leichtman, 2000). For instance, Han et al (1998) demonstrated that the narratives of Chinese and Korean children were similarly less detailed in terms of specific events than those of American children.…”
mentioning
confidence: 99%
“…The adopted practices among educators from G1 mark a conception of development which considers the child to acquire social and cognitive abilities through interactions and stimulation organised by the educators. According to some scholars of child development, this would be a more adequate practice for children's education (Brann, 2010;Keller et al, 2007;Rotenberg & Vargas, 2004). Data indicate that educators from G1 invested more in the quality of the interactions during the feeding situations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Piccinini, Frizzo, Alvarenga, et al (2007) and Keller et al (2007), these practices are defined as authoritarian and can bring consequences for the child's learning in reference to rule assimilation and its importance for the development of social abilities. Nevertheless such practice was more evident with children younger than two years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such trajectories have been described as moving towards the socialization of either autonomous/independent selves or towards interdependent selves. Findings in several cross-cultural investigations, carried out by Keller and her colleagues (Keller et al, 2006;Keller et al, 2007;Keller, Borke, Lamm, Lohaus, and Yovsi, 2011; see also Keller, 2007), are representative of these notions of different trajectories of development of the self. In these studies, Keller and colleagues analyzed general orientations concerning parental beliefs, and values among parents of several distinct cultures (German, Euro-American, Greek, Indian, Chinese, Mexican and Costa Rican).…”
Section: Parental Investment and Carementioning
confidence: 93%